PEMBERDAYAAN JEMAAT HKBP PANTI RESORT PASAMAN MELALUI PENDIDIKAN DAN LITERASI UNTUK MENINGKATKAN PERTUMBUHAN IMAN YANG BERTANGGUNG JAWAB - Rika Simanjuntak; Udur Ernita Aritonang; Romauli Sianturi; Rumanti Hutagaol; Sartika Medianti Sihite (Merwinspy Publisher, 2026)
This community service program aimed to empower the congregation of HKBP Panti Resort Pasaman through education and literacy activities to strengthen responsible faith growth, particularly among youth and Sunday school participants. The program was motivated by challenges in the digital era that affect spiritual quality, self-control, and religious literacy among young generations. The activity involved 45 participants, consisting of 20 adolescents, 15 Sunday school children, and 10 adult congregation members. A participatory method was employed through three stages: preparation, implementation, and evaluation. Program activities included worship services, Bible study sessions, spiritual retreats, pastoral visits, and spiritual-social literacy training. Indicators of success were measured through attendance records, participant observation, and pretest-posttest questionnaires on spiritual understanding. The results showed that average participation in church activities increased from 62% to 84% (+22%), while participants’ understanding of faith values and spiritual literacy improved from 68% to 87% (+19%). In addition, participants demonstrated stronger awareness of balancing digital life with spiritual responsibilities and greater enthusiasm for church involvement. Therefore, education- and literacy-based empowerment proved effective in strengthening the church’s role as a center for spiritual development and character formation in society.